Ergonomic analysis and strategies for compliance with NOM-036-1-STPS-2018 in three production areas and an administrative area in a Mexican agroindustrial metalworking company. (AACINI - International Journal of Industrial Engineering, 2024)
The project was carried out in a metalworking company, which manufactures agricultural machinery, in Lagos de Moreno, Jalisco, Mexico. An ergonomic risk analysis was carried out in the main process areas in activities that involve manual handling of loads: area of injectors, blowers, and moldable metals (ISMM), assembly of agricultural machinery and spare parts (EMAR) and Tooling (HE), and in general administrative area (PCP). Evaluations of the level of dysergonomic risk were carried out, in accordance with NOM-036-STPS-2018 and support in the MAC, RULA, ROSA methods. Some strategies were implemented to reduce the level of risk, work standards were generated for the manual handling of loads, the ergonomics program was developed in accordance with the official Mexican standard, which is mandatory. A simulation was carried out in PROMODEL software, of the improvements planned to be implemented later. Finally, the level of dysergonomic risk decreased by 18% in the jobs with the highest level of diagnosis.
Keywords: Ergonomics; agroindustry; risk assessment; compliance with Mexican standards